PENGARUH KNOWLEDGE SHARING TERHADAP KNOWLEDGE MANAGEMENT PEGAWAI DI SEKRETARIAT DERAH KABUPATEN KERINCI YANG DIMEDIASI OLEH TRANSFER OF TRAINING - Ayu Esteka Sari (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine the effect of Knowledge Sharing on Knowledge Management of Employees at the Regional Secretariat of Kerinci Regency, the effect of Transfer of Training on Knowledge Management of Employees at the Regional Secretariat of Kerinci Regency, the effect of Transfer of Training in moderating Knowledge Sharing on Knowledge Management at the Regional Secretariat of Kerinci Regency. The sample in this study were 112 respondents, who used a full sampling technique. Model technique using Structural Equation Model (SEM) using AMOS. Based on the results of the study, it can be concluded that the Hypothesis Testing of Knowledge Sharing on employee knowledge management at the Regional Secretariat of Kerinci Regency is the result of CR = 12.646 and P = 0.000. It was found that Knowledge Sharing has a positive and significant effect on employee knowledge management at the Regional Secretariat of Kerinci Regency and is acceptable. The magnitude of the influence of Knowledge Sharing on employee knowledge management at the Regional Secretariat of Kerinci Regency is 0.914 or 91.4% so that knowledge sharing support is needed to improve knowledge management